Loss of Trust Among First Nation People: Implications when Implementing Child Protection Treatment Initiatives - Thibodeau, Steven; Peigan, Faye North (First Peoples Child & Family Review, 2007)
Social workers and other health care providers have been asked to develop and implement innovative and culturally sensitive treatment initiatives in First Nation communities. However, because of traumatization and oppression, many First Nations people face troubling psycho-social issues which have resulted in a diminished capacity to trust. If this loss of trust is not dealt with skillfully, it can impede the ability of social workers to implement initiatives. Through a process of person-centred interviewing, 36 participants identiﬁed four levels of trust that have been diminished among many First Nations people. The impact of this phenomenon on the development and implementation of community based initiatives is discussed in this article.